A guided matter-wave Sagnac interferometer - Bishop, Thomas (2019)
This thesis presents the experimental scheme for a guided cold atom Sagnac interferometer. Although atom interferometers have become an established method for precision measurements, a feasible clock-scheme based on fully guided atoms has yet to be realised. Radio frequency potentials, generated by a chip, provide a means to create a compact, fully controllable guided atom interferometer. The experimental infrastructure for a rubidium cold atom system is built and characterised. A chip-based atomic clock scheme is presented, utilising state-dependent guiding around a ring shaped trap. The chip design to form the trap and operate the interferometer is presented, and a vacuum compatible PCB has been designed and commercially manufactured to provide atomic transport and compression towards an atom chip. This project is part of the larger MatterWave project. In collaboration with Birmingham and Crete, the Matterwave project aims to develop ultra-sensitive matter-wave interferometry for compact devices.